2021
DOI: 10.1007/s10493-021-00629-z
|View full text |Cite
|
Sign up to set email alerts
|

Using MALDI-TOF mass spectrometry to identify ticks collected on domestic and wild animals from the Democratic Republic of the Congo

Abstract: Matrix-assisted laser desorption/ionization mass spectrometry (MALDI-TOF MS) has recently emerged as an alternative to morphological and molecular tools to identify tick species. In this study, we set out to evaluate and confirm the ability of MALDI-TOF MS to identify different species of ticks collected in the Democratic Republic of the Congo and preserved in 70% ethanol. A total of 575 ticks, of which 530 were collected from domestic pigs and 45 from wild animals, were subjected to MALDI-TOF MS analysis to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The Anaplasma strain was most closely related to a strain found in Lemniscomys striatus in Franceville in Gabon (Mangombi et al, 2021). The Ehrlichia strain was mainly similar to a strain detected in a Rhipicephalus tick (family Ixodidae) collected from livestock in Kisangani, Democratic Republic of Congo (Ngoy et al, 2021). Similar to Bartonella, we found that adult M. natalensis were more likely to be infected with Anaplasma than juveniles, which can again be explained by the long-lasting duration of infections and horizontal transmission via a vector.…”
Section: Discussionmentioning
confidence: 70%
“…The Anaplasma strain was most closely related to a strain found in Lemniscomys striatus in Franceville in Gabon (Mangombi et al, 2021). The Ehrlichia strain was mainly similar to a strain detected in a Rhipicephalus tick (family Ixodidae) collected from livestock in Kisangani, Democratic Republic of Congo (Ngoy et al, 2021). Similar to Bartonella, we found that adult M. natalensis were more likely to be infected with Anaplasma than juveniles, which can again be explained by the long-lasting duration of infections and horizontal transmission via a vector.…”
Section: Discussionmentioning
confidence: 70%
“…Our findings might have important implications for future helminth diagnosis in epidemiologic studies. Indeed, MALDI-TOF MS is a widely used diagnostic tool in microbiologic routine diagnosis [21,22], which will also be increasingly available in laboratories of low-and middle-income countries [23]. Besides the identification of bacteria and fungi, this technique has also been successfully used for the differentiation of ticks and fleas [24], mosquitos [25], lice [26], and more recently, different helminths of medical and veterinary importance [13].…”
Section: Discussionmentioning
confidence: 99%
“…The extracted compounds, mainly consisting of small cytosolic proteins and peptides (Ryzhov & Fenselau, 2001), are measured by matrix‐assisted laser desorption ionization time of flight mass spectrometry (MALDI‐TOF MS) producing species‐specific mass spectra, allowing the differentiation and, in combination with a reference database, the identification of specimens. Within the last 10 years several proof‐of‐concept studies on metazoans have revealed its general applicability for invertebrates (Murugaiyan & Roesler, 2017), specifically for insects (Campbell, 2005; Chavy et al, 2019; El Hamzaoui et al, 2018; Hasnaoui et al, 2022; Lawrence et al, 2019) and arachnids (Diarra et al, 2017; Gittens et al, 2020; Karger et al, 2019; Ngoy et al, 2021), which are relevant as vectors and pests. Far fewer studies have addressed taxa less relevant to human health.…”
Section: Introductionmentioning
confidence: 99%